2023
DOI: 10.3389/fnut.2023.1169675
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, bioactive components and health properties of the milpa triad system seeds (corn, common bean and pumpkin)

Abstract: The milpa system is a biocultural polyculture technique. Heritage of Mesoamerican civilizations that offers a wide variety of plants for food purposes. Corn, common beans, and pumpkins are the main crops in this agroecosystem, which are important for people’s nutritional and food security. Moreover, milpa system seeds have great potential for preventing and ameliorating noncommunicable diseases, such as obesity, dyslipidemia, type 2 diabetes, among others. This work reviews and analyzes the nutritional and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…The Milpa diet is a traditional Mexican food pattern that includes foods consumed since prehispanic times, mainly corn/maize, beans, squash, chili peppers, tomato, cactus pads, cacao, and avocado ( 28 ). In observational studies, adherence to this food pattern has shown health benefits that may be attributed to phenolic compounds, saponins, carotenoids, and galacto-oligosaccharides, which act as prebiotics and thus modulate gut microbiota and systemic inflammation ( 29 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Milpa diet is a traditional Mexican food pattern that includes foods consumed since prehispanic times, mainly corn/maize, beans, squash, chili peppers, tomato, cactus pads, cacao, and avocado ( 28 ). In observational studies, adherence to this food pattern has shown health benefits that may be attributed to phenolic compounds, saponins, carotenoids, and galacto-oligosaccharides, which act as prebiotics and thus modulate gut microbiota and systemic inflammation ( 29 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…With a growing interest in beneficial substances beyond human nutrition, some review and research articles have recently been published on the bioactive compounds involved in milpa systems. These studies analyzed the bioactive and chemical composition [ 40 , 80 , 81 ] of the species involved, and others studied the nutritional and health benefits of milpa system seeds assessed in preclinical and clinical trials [ 82 ].…”
Section: Modifying the Nutritional Profile In Intercropping Systemsmentioning
confidence: 99%
“…Further research is necessary into how we might influence the metabolic pathways of interest in order to produce specific bioactive compounds and be able to test their bioactivity on human health. To this end, the content of the bioactive compounds of several species grown in a monoculture is being reviewed more effectively to obtain a nutraceutical benefit in humans [ 40 , 82 , 93 ], and these studies could pave the way to obtaining a more complete understanding of metabolic pathways and the different types of stress that activate them. This could be helpful for comparing and improving the amount of these bioactive compounds or macronutrients in intercropped systems under other conditions.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The origins of this dietary pattern date back to pre-Hispanic times, when milpas or cornfields were utilized as a productive and sustainable agricultural system to grow local seeds [20,21]. Traditionally, the main crops were corn/maize, common beans, and pumpkins/squashes, which, along with chilies, are the basis of the Dieta de la Milpa [20].…”
Section: Components Of the Dieta De La Milpa Dietary Patternmentioning
confidence: 99%
“…A dietary pattern for Mesoamerica (Central Mexico and Central America) called Dieta de la Milpa or Diet of the Cornfield was recently described [ 20 ]. This dietary pattern is characterized by a diet based on the consumption of corn/maize ( Zea mays L.), common beans ( Phaseolus vulgaris L.), a variety of pumpkins/squashes ( Curcubita pepo maxima and moschata ), and chilies ( Capsicum annum and frutescens ) [ 20 , 21 ]. The diet is complemented by a diet high in vegetables and fruits commonly grown in the Mesoamerican region, including tomatoes ( Solanum lycopersicum L.), starchy vegetables (such as sweet potato and yuca), other whole grains and legumes, fish, water, and avoidance of ultra-processed foods, red meat, and artificial sweeteners [ 20 ].…”
Section: Introductionmentioning
confidence: 99%